Morphology, Cell Division, and Phylogeny of Uroleptus longicaudatus (Ciliophora, Hypotricha), a Species of the Uroleptus limnetis Complex. (20th December 2015) - Chen, Lingyun; Lv, Zhao; Shao, Chen; Al‐Farraj, Saleh A.; Song, Weibo; Berger, Helmut
Abstract: A Chinese population of the little‐known freshwater hypotrich Uroleptus longicaudatus was investigated with emphasis on its living morphology and infraciliature. The characteristic, tripartite body consists of a narrowed (cephalized) anterior portion, a slender trunk, and a long, slender, and strongly contractile tail occupying up to 30% of body length. Contracted specimens with a tail length of about 12% closely resemble Uroleptus limnetis which has, like U. longicaudatus, its type locality on the East Coast of the United States so that it cannot be excluded that these two species are synonymous. Thus, we propose to subsume these and few other little‐known species, which are not clearly distinguishable at the present state of knowledge, as U. limnetis complex. The morphogenesis of U. longicaudatus proceeds as in most congeners. The phylogenetic analyses reveal that Uroleptus is a monophyletic group, but due to the lack of detailed morphological data of the populations sequenced so far, the relationships within this taxon remain obscure. For the objective determination of the tail length of hypotrichs, we propose the "1/3‐method", which says that the tail commences at that body width which corresponds one‐third of the maximum width. Paruroleptus ophryoglena Gelei, 1954 is transferred to Uroleptus : Uroleptus ophryoglena (Gelei, 1954) comb. nov.